Shaping the future for quality: Initiating active surveillance as foundation to drive improvement for health care-associated infections - Khuan, Ng Wai; Springhorn, Helge (International Journal of Infection Control, 2012)
Prior to April 2008, there was only total house surveillance. In total (or whole house) surveillance, all types of health care-associated infections (HCAIs) are monitored in the entire organization of Mafraq Hospital. overall infection rates were not adjusted for specifc infection or injury risks. The trends were not measured over time; no comparisons were made between groups, either interhospital or intrahospital, nor was benchmarking done. A thorough facility-wide infection prevention and control risk assessment was performed in March 2008 by the only certifed, newly employed infection preventionist. After completion of the risk assessment, the data and information was collated and presented. the infection preventionist proposed the urgent implementation of an active targeted and modifed total house surveillance program to monitor all patients admitted to Mafraq Intensive Care Units (ICUs). total house surveillance was also modifed to target only populations in intensive care units. A surveillance plan was developed with emphasis on the following: central line-associated bloodstream infection (CLABSI), ventilator-associated pneumonia (VAP), catheter-associated urinary tract infection (CAUTI) and healthcare-associated multidrug-resistant organism (HA-MDRO). The active targeted and modifed total house surveillance program was initiated only within Mafraq intensive care units in April 2008. Since then, hand hygiene compliance monitoring and educational program were gradually implemented.As active surveillance improved within Mafraq ICUs, it was noted that, during this period, healthcare-associated infection rates (i.e., CLABSI, VAP, CAUTI, and HA-MDRO in Mafraq ICUs decreased from 2nd quarter 2008 till 2nd quarter 2012.The limitations of this study include absence of comparable data before active surveillance initiated in April 2008, lack of information on population variability. The evidence from the active targeted and modifed total house surveillance in Mafraq ICUs showed a decrease in healthcare-associated infections since the initiation in 2nd quarter 2008 till 2nd quarter 2012. Therefore, it can be concluded that HCAIs can be signifcantly impacted through the implementation of an active surveillance program.